2021
DOI: 10.1111/chso.12495
|View full text |Cite
|
Sign up to set email alerts
|

Gamification and family leisure to alleviate the psychological impact of confinement due to COVID‐19

Abstract: This study presents a quasi‐experimental longitudinal mixed‐methods research about the participation in leisure activities, physical activity, and games, as part of the family leisure programme (“Lunae Magic School”) for Spanish families with children under 12 years old during COVID‐19 lockdown. The impact on parents and their perception of the psychological well‐being of their children is evaluated. The results show that leisure activities reduce the parent's anxiety levels measured with STAI scale ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…A range of support services and modes of delivery, such as telehealth services, after hours phone services, and peer support, are needed to meet the varied needs and accessibility challenges for parents and children, particularly those who are socioeconomically disadvantaged (Golberstein et al, 2020 ; Lee, 2020 ; Wang et al, 2020 ). In addition to mental‐health specific support services, there is evidence that online family leisure games can serve to mitigate the anxiety and stress associated with home confinement (Manzano‐León et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A range of support services and modes of delivery, such as telehealth services, after hours phone services, and peer support, are needed to meet the varied needs and accessibility challenges for parents and children, particularly those who are socioeconomically disadvantaged (Golberstein et al, 2020 ; Lee, 2020 ; Wang et al, 2020 ). In addition to mental‐health specific support services, there is evidence that online family leisure games can serve to mitigate the anxiety and stress associated with home confinement (Manzano‐León et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, this subject gains even more relevance, since the COVID-19 pandemic brought numerous changes into people's routines, enhancing telework (Mendonça et al, 2022 ) and lighting up discussions about productivity and motivation (Prodanova & Kocarev, 2022 ), together with well-being and mental health of people within this new global reality (Carillo et al, 2021 ; Giorgi et al, 2020 ; Impact et al, 2021 ; Shahriarirad et al, 2021 ). Gamification, during COVID-19 quarantine, showed positive results for the well-being and relief of the tension of people in confinement (Manzano-León et al, 2021 ) and showed a potential positive effect on leveraging both motivation and employee engagement (Pura, 2022 ) . As discussed in above, serious games and gamification have the general purpose of improving productivity, motivation, well-being, and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…It can be considered a complex human need with various adaptive purposes (1). These include improving physiological and psychological functioning (2), enjoying entertainment and pleasant moments (3), seeking distraction from daily concerns and stressful work (4), spending time with family, friends, and acquaintances (5,6), coping with social crises (7), and even informal learning (8). In addition, leisure seems to constitute one of the most fundamental human behaviors and a part of our daily routines since the early stages of human evolution (9,10).…”
Section: Introductionmentioning
confidence: 99%